2011
DOI: 10.1002/marc.201100646
|View full text |Cite
|
Sign up to set email alerts
|

Optically Active Helical Substituted Polyacetylenes Showing Reversible Helix Inversion in Emulsion and Solution State

Abstract: This Communication reports two substituted polyacetylenes that can adopt helical structures of preferential screw sense in both emulsion (nanoparticle) and solution; however, the handedness of the macromolecular helices is just opposite in the two states. More interestingly, the helical screw sense of the polymers demonstrated a reversible transition between the two states. The unprecedented findings are of significant importance for acquiring new insights into helical polymers and for developing novel advance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 44 publications
1
8
0
Order By: Relevance
“…Moreover, compared with the polymer emulsion ( λ max , 350nm), pronounced red shifts took place in the CD and UV‐Vis absorptions of polymer solution ( λ max , 390 nm). The red shifts resulted from the prolonged effective conjugation length in helical polymer chains in solution state, as ever observed and discussed in detail in our earlier studies . We further characterized the copolymers with different compositions in THF by CD technique, and the corresponding CD spectra are shown in Supporting Information Figure S3.…”
Section: Resultssupporting
confidence: 59%
“…Moreover, compared with the polymer emulsion ( λ max , 350nm), pronounced red shifts took place in the CD and UV‐Vis absorptions of polymer solution ( λ max , 390 nm). The red shifts resulted from the prolonged effective conjugation length in helical polymer chains in solution state, as ever observed and discussed in detail in our earlier studies . We further characterized the copolymers with different compositions in THF by CD technique, and the corresponding CD spectra are shown in Supporting Information Figure S3.…”
Section: Resultssupporting
confidence: 59%
“…In the studies of Deng and coworkers, 86 the polymer particles of monomer 3(R or S) showed an opposite sign in CD effects when 60 compared to the corresponding polymers obtained by solution polymerization. Namely, "chirality" inversion occurred to the polymer particles.…”
Section: (3) Chirality Inversionmentioning
confidence: 94%
“…However, this is not always true for all the polymer emulsions and PCPs. A pair of polymer emulsions (polymer 3 S and polymer 3 R , derived from M 3 S and M 3 R , respectively, in Figure ) exhibited CD signals in the opposite sign to that of the same polymer solution . It is well known that the CD signal of the polymer emulsion resulted from the predominant one‐handed macromolecular helicity of the polymer chains forming the nanoparticles .…”
Section: Particles Of Chiral Polymersmentioning
confidence: 97%